Multi-locus phylogeny of southern African Acontias aurantiacus (Peters) subspecies (Scincidae: Acontinae) confirms the presence of three genetically, geographically and morphologically discrete taxa - Pietersen, Darren W.; Scholtz, Clarke H.; Bastos, Armanda D.s. (Zootaxa, 2018)
Acontias aurantiacus (Peters) presently consists of five subspecies that are largely restricted to the coastal regions and offshore islands of Mozambique and northern South Africa, with subspecies being defined on the basis of morphological differences and/or parapatric distributions. In this study one nuclear (RAG1) and two mitochondrial (cyt b and 16S) genes of 30 individuals sampled from four Mozambican and five South African localities were used to assess the taxonomic relationships of three mainland A. aurantiacus subspecies. Our analyses suggest that A. aurantiacus is a species complex that is sister to A. bicolor (Hewitt), A. cregoi (Boulenger) and A. rieppeli (Sternfeld). Our molecular results support other lines of evidence (consistent morphological differences and parapatric distributions between the subspecies) in suggesting that each of these subspecies are taxonomically distinct. In light of this, and supported by the genetic distances between these subspecies which exceed those of other recognised Acontias species, we propose elevating A. fitzsimonsi (Broadley) and A. parietalis (Broadley) to specific status. Our results further suggest that the melanistic and typically-coloured forms of each taxon are nested within the same clades, supporting previous contentions that melanistic individuals are not cryptic taxa.